2900 Square Degree Search for the Optical Counterpart of Short Gamma-Ray Burst GRB 180523B with the Zwicky Transient Facility. (20th February 2019) - Coughlin, Michael W.; Ahumada, Tomás; Cenko, S. Bradley; Cunningham, Virginia; Ghosh, Shaon; Singer, Leo P.; Bellm, Eric C.; Burns, Eric; De, Kishalay; Goldstein, Adam; Golkhou, V. Zach; Kaplan, David L.; et al.
Abstract: There is significant interest in the models for production of short gamma-ray bursts (GRBs). Until now, the number of known short GRBs with multi-wavelength afterglows has been small. While the Fermi GRB Monitor detects many GRBs relative to the Neil Gehrels Swift Observatory, the large localization regions makes the search for counterparts difficult. With the Zwicky Transient Facility (ZTF) recently achieving first light, it is now fruitful to use its combination of depth ( m AB  ∼ 20.6), field of view (≈47 square degrees), and survey cadence (every ∼3 days) to perform Target of Opportunity observations. We demonstrate this capability on GRB 180523B, which was recently announced by the Fermi GRB Monitor as a short GRB. ZTF imaged ≈2900 square degrees of the localization region, resulting in the coverage of 61.6% of the enclosed probability over two nights to a depth of m AB  ∼ 20.5. We characterized 14 previously unidentified transients, and none were found to be consistent with a short GRB counterpart. This search with the ZTF shows it is an efficient camera for searching for coarsely localized short GRB and gravitational-wave counterparts, allowing for a sensitive search with minimal interruption to its nominal cadence.